Association of chronic nasal symptoms with dyspnoea and quality‐of‐life impairment in chronic obstructive pulmonary disease. Issue 3 (15th December 2013) - Caillaud, Denis; Chanez, Pascal; Escamilla, Roger; Burgel, Pierre‐Régis; Court‐Fortune, Isabelle; Nesme‐Meyer, Pascale; Deslee, Gaëtan; Perez, Thierry; Pinet, Christophe; Roche, Nicolas; ,
Abstract Background and objective Previous studies suggested that chronic nasal symptoms (CNS) are frequent in chronic obstructive pulmonary disease (COPD) subjects, but their contribution to dyspnoea and quality‐of‐life (QoL) impairment is not clearly established. Methods Data from the French COPD cohort 'Initiatives bronchopneumopathie chronique obstructive' were analyzed to assess the frequency of CNS (rhinorrhea, obstruction, anosmia) in COPD patients and analyze their impact and associated risk factors. Univariate and multivariate analyses were performed to assess the relationship between CNS with sociodemographic and anthropometric characteristics, risk factors, respiratory symptoms, spirometry, QoL (Saint George's respiratory questionnaire (SGRQ)), dyspnoea (modified Medical Research Council (mMRC) scale), mood disorders (Hospital Anxiety and Depression Scale (HADS)), number of exacerbations and comorbid conditions. Results CNS were reported by 115 of 274 COPD subjects (42%). Among them, rhinorrhea and nasal obstruction were reported by 62% and 43%, respectively. In multivariate analysis, COPD patients with CNS had higher SGRQ total scores, corresponding to worse QoL (P = 0.01), while no independent association was found with exacerbations, lung function and HADS. Among SGRQ domains, an independent association was found with the activity score (P = 0.007). When SGRQ score was forced out of the model to avoid redundancy, mMRC score was independently associated with CNS (P = 0.01). Among risk factors, cumulative smoking, hay fever and atopic dermatitis but not occupational exposures were independently associated with CNS. Conclusions In this group of COPD subjects, CNS were frequently observed and associated with dyspnoea and poorer QoL. CNS should be systematically assessed and could be a potential target in the management of COPD.